Kapabilitas Organisasi dan Keunggulan Kompetitif: Peran Mediasi Kapabilitas Inovasi Pada Organisasi Masyarakat Sipil (OMS) - Bintang Mikail Subuh; Kesi Widjajanti; Indarto Indarto (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study aims to analyze financial and technological capabilities as organizational capabilities that can be achieved through competitive advantage and mediated through innovation capabilities. This study used a judgment sampling method with 58 questionnaire responses from representatives of Civil Society Organizations (CSOs) in Indonesia, which were analyzed using PLS-SEM. The results indicate that organizational capabilities, including financial and technological capabilities, do not influence competitive advantage in CSOs. However, innovation capability plays a positive role in the effect of technological capability on competitive advantage. This study implies that digitalization creates an innovation capability to foster technological capability and competitive advantage in Indonesia CSOs.